Preoperative, Intraoperative and Postoperative Assessment of Pelvic Organ Prolapse by Pelvic Organ Prolapse Quantification System and Surgical Outcome - Noor, Serajun; Shahnaj, Sharmin; Aklima, Sultana; Monira, Jamal; Farjana, Shurovi; Taniza, Jabin (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Pelvic organ prolapse (POP) is a common disease of middle aged and elderly women with an incidence of 7-10% and life time risk for surgery 11 to 20%. Assessing pelvic organ prolapsed in an objective, reproducible and applicable method is essential to have successful surgical outcome. Aim of the study was preoperative, intraoperative pre and postsurgical as well as postoperative assessment of pelvic organ prolapse by POP- Q system in patients undergoing reconstructive surgery and measure optimum surgical outcome stage 0 (Q<-1), Tvl > 4 cm and Genital hiatus (3 to 3.4cm) to prevent recurrence (POP-Q stage > -1) and dyspareunia (Pb d”3 cm). Methods : This was hospital based Prospective study done with 250 patient diagnosed as pelvic organ prolapse at OPD. Excluding 14 patients 236 had surgery in Chattagram Metropolitan Hospital during January 2010 to December 2019. POP-Q measurement was done with Valsalva before anesthesia, intraoperative after anesthesia pre and postsurgical and postoperatively in follow up visit within three months of surgery by same surgeon. All POPQ measurement were done by same surgeon using a wooden Spatula marked in cm (POP-Q popsicle stick). All measurement were recorded in grid form and preoperative & presurgical POP-Q staging was done. The result was then summarized as mean and SD for numerical variable and percentage for categorical variable. Result : A total 236 patient had surgery, 233 had vaginal hysterectomy with Apical vaginal suspension with uterosacral ligament and sacrospinous fixation was done in 3 patients with vault prolapse. Mean age was 51 ± 5SD years (51 to 60 years 51%), 84% sexually active, low socioeconomic group (68%), multiparous 100% mean parity 4 ± 2SD (e” 6 62%), 95% had vaginal delivery with history of home delivery 89%, resuming house hold work within two weeks of delivery in 97% cases. Most were postmenopausal 96%. All intraoperative presurgical measurement except Pb and Tvl showed significant higher descent as compared to preoperative finding before anesthesia, mean difference were Aa 0.7, Ba1.6, C 1.6, Ap 0.25 Bp 1.6 D1.6 Gh. 8cm with highest descent in Ba C, D Bp. Immediate postsurgical measurement all patient showed optimum anatomical outcome (stage 0). But follow up within 3 month (10 to 90 days) 13 patient showed satisfactory anatomical outcome (stage 1 Q<-1)) with no recurrence (Q>-1) nor dyspareunia. Total vaginal length and Pb no change in measurement before and after anesthesia but Tvl reduced by 2.3 cm and Pb increased by .3cm postsurgical. Presurgical measurementof Gh increased by. 8cm but reduced to 3.5 cm postsurgical. No significant difference in postsurgical intraoperative measurements during follow up within 3 months except Gh (3.2 cm) which is narrower even with valsalva menovure. Conclusion : POP-Q technique in assessment of Pelvic organ prolapse was anatomically site specific and is with good reproducibility and less intra and inter observer variation. Significant difference in descent alert surgeon to plan surgical technique to have optimum anatomical outcome and prevent recurrence and dysparunea. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 109-118